Sustainable practices in cashew supply chains: a multi-case study in the scenario of small and medium-sized companies - Jales, Frediano da Silva; Mulling Neutzling, Daiane; Dias, Gustavo Picanço (Sustainability in Debate, 2022)
This research analysed the motivation and difficulties behind adopting sustainable practices in small and medium-sized companies in the cashew industry supply chains (SMEs). The literature provides the main concepts of sustainable practices, motivation and difficulties in adopting practices in the context of SMEs. A multiple case study methodology was used. Two supply chains processing cashew nuts and cashew pulp in the state of Ceará were analysed. The implications of managing sustainability along the supply chain of SMEs, when they are still focal companies, lie in the fundamental importance of partnerships with research and business assistance organisations and the trust established with suppliers. To corroborate the research findings, the literature recognises that relationships are highly personal in SME supply chains.